300 Jahre Robinson Crusoe Ein Weltbestseller und seine Rezeptionsgeschichte - Frimmel, Johannes; Haug, Christine; Bell, Bill (De Gruyter, 2022)
The year 2019 marked the 300th anniversary of Daniel Defoe's Robinson Crusoe. His novel was a huge success right away and was soon followed by bootlegs and translations. With the robinsonade, an independent genre of adventure literature was born. These contributions examine the novel within the context of bookselling history, provide new interpretations, and shed light on its multifaceted adaptation history up into the twenty-first century.